TI_GERICHTE 52.2008.75 vom 16. April 2010 , Licenza edilizia. Ampliamento di uno stabilimento non conforme alla zona di situazione - TI Tribunale d'appello (2010)
Licenza edilizia. Ampliamento di uno stabilimento non conforme alla zona di situazione